KONIEC MORSZTYNA. PRZYCZYNEK DO DZIEJÓW PRAWA RZYMSKIEGO W POLSCE - Palmirski, Tomasz (Zeszyty Prawnicze, 2017)
THE END OF MORSZTYN. A CONTRIBUTION TO THE HISTORY OF THE ROMAN LAW IN POLAND Summary The lawsuit of Jan Andrzej Morsztyn at the Diet Court in 1690, and first of all, the issue of applying the rules provided by the Roman law with regard to the judicial oath of the sued party, has been discussed in the literature of the subject. However, the researchers have limited themselves to the statement that this fact took place. They did not prove that the Roman law, and precisely, the Justinian law, knew the concept of an oath made in writing, to which persons acting as Morsztyn’s substitutes in the lawsuit referred to. The author, considering relevant regulations comes to a conclusion that the Justinian law did not provide for a possibility to take an oath in writing. On the other hand, Polish law did not provide for such a possibility either since an oath taken in land cases always assumed a form of an oral oath. Therefore, taking into account the political situation in which the lawsuit against Morsztyn, king Jan Sobieski IITs opponent, took place, it should be assumed that the decision which allowed a written form of an oath was a sign of the judges’ common sense (rejecting the recognition of the written form in the context of restitution of the crown’s jewels by the accused, could only increase the number of Morsztyn’s followers) and the law-making activity of the Diet Court rather than an example of applying the Justinian law.